Dialectics of Globalization and Local Identity Resistance: Cultural Negotiation in Contemporary Indonesian Society (International Journal of Economics Management and Social Science, 2026)
This article examines the dialectical relationship between globalization forces and local identity resistance in contemporary Indonesian society, focusing on cultural negotiation processes. Globalization, understood as intensification of worldwide social relations linking distant localities, creates tensions with local cultural identities rooted in specific territorial communities. Indonesia's cultural diversity, with over 300 ethnic groups and 700 languages, provides particularly rich context for examining how local communities negotiate between global cultural flows and traditional identity markers. Drawing on recent ethnographic research and cultural studies, this analysis explores how Indonesian communities employ diverse strategies including syncretism, selective appropriation, strategic essentialism, and creative hybridization to maintain cultural distinctiveness while engaging global modernity. The findings reveal that rather than simple homogenization or polarization, Indonesian cultural dynamics exhibit complex negotiations wherein local actors actively shape globalization processes to serve community purposes. Case studies from West Java, Bali, and Papua demonstrate varying patterns of cultural negotiation reflecting different historical trajectories, economic positions, and political contexts. This article contributes to globalization studies by demonstrating that local communities are not passive recipients of global forces but active agents constructing hybrid cultural formations through strategic negotiation.Keywords: Globalization, local identity, cultural resistance, cultural negotiation, Indonesia, hybridization, glocalization, cultural diversity